2015
DOI: 10.3109/14764172.2015.1007065
|View full text |Cite
|
Sign up to set email alerts
|

Intense focused ultrasound for facial tightening: Histologic changes in 11 Patients

Abstract: Intense focused ultrasound can be used as a non-invasive skin tightening technique in Asian patients. It induced collagen generation in the dermis and fat layers and was effective and safe in our study population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…It produces small, micro‐thermal lesions at well‐defined depths in the dermis up to the fibromuscular layer, causing thermally induced tissue contraction and tissue coagulation with subsequent collagenesis . Previous studies have demonstrated ultimate improvement of facial lifting and tightening took place over 2‐3 months . In addition, needle‐free transcutaneous pneumatic injection of specific solutions was recently reported to be safe and effective for treating various cutaneous scars and wrinkles .…”
Section: Introductionmentioning
confidence: 99%
“…It produces small, micro‐thermal lesions at well‐defined depths in the dermis up to the fibromuscular layer, causing thermally induced tissue contraction and tissue coagulation with subsequent collagenesis . Previous studies have demonstrated ultimate improvement of facial lifting and tightening took place over 2‐3 months . In addition, needle‐free transcutaneous pneumatic injection of specific solutions was recently reported to be safe and effective for treating various cutaneous scars and wrinkles .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, visualization allows treatment to target the desired tissue, customizing it according to the rationale of the expected result in each layer with increased safety. 6–8 …”
Section: Introductionmentioning
confidence: 99%
“…Although there is limited data in the literature about the MFU devices other than Ulthera, the majority of studies evaluating MFU effects on improving skin laxity have shown encouraging results 2‐9 . As far as we know there is no report on evaluating the effect of a newer MFU device (Microson, Cosmoplus Co, Sungnam, Korea) in lower facial laxity.…”
Section: Introductionmentioning
confidence: 99%
“…At 90 and 180 days, subject GAIS scores showed 75% and 77.8% of subjects indicated that they noticed improvement in face and neck characteristics 4. In 2015, Suh et al reported 63.6% of subjects had clinical improvement 2 months after the application of a different MFU device (Doublo, HIRONIC Co., Sungnam, Korea) with a total 440 lines for cheeks and submentum 5. Increased collagen fibers in the lower dermis and between fat layers were also shown histopathologically in the same study.…”
mentioning
confidence: 99%